Project Report on Interfacing of Positional Encoder using Emdat 2.2 Protocol and RS485 Interface - POORNIMA H R, SHAMBHAVI and YESHASHWINI (2014)
INTERNAL GUIDE: E KRISHNA KUMAR, MVJCE
Keywords: Protocol and RS485 Interface